(untitled) (Asian Journal of Social Science Studies, 2021)
This study analyzes the factors that affect the competitiveness of ASEAN-5 countries in terms of Labor Productivity, Net Exports, Investment, Inflation and Exchange Rates in two periods, namely the ASEAN internal crisis and the global crisis using the times series data from 1997-2017, then analyzed with the regression analysis model. The results showed that the labor productivity of the 1997-2008 period had a positive and significant effect on the competitiveness of ASEAN-5, as well as the period of 2008-2019, labor productivity had a positive and significant effect on the competitiveness of ASEAN-5. The net export period of 1997-2008 had a negative and not significant effect on the competitiveness of ASEAN-5, as well as the period of 2008-2017, the net export had a negative and not significant effect on the competitiveness of ASEAN-5. The investment period of 1997-2008 has a negative and not significant effect on the competitiveness of ASEAN-5, while the period 2008-2017 has a positive and not significant effect on the competitiveness of ASEAN-5. Inflation in the 1997-2017 period had a negative and insignificant effect on the competitiveness of ASEAN-5, as well as the 2008-2017 inflation period had a negative and not significant effect on the competitiveness of ASEAN-5. Exchange rates for the period 1997-2008 have a negative and insignificant influence on the competitiveness of ASEAN-5, as well as the 2008-2017 period, which has a negative and insignificant effect on the competitiveness of ASEAN-5.